Practical approaches for retrofitting plug flow digester and process control to maximize hydrolysis and methane yield from piggery waste. Issue 4 (August 2021) - Chetawan, Worakan; Saritpongteeraka, Kanyarat; Palamanit, Arkom; Chaiprapat, Sumate
Abstract: This study demonstrates and quantifies biomethanation improvements from practical schemes of retrofitting anaerobic plug flow (PF) digester for piggery wastewater (1% total solids concentration). First, batch assays were performed to seek the optimal scenario for substrate solubilization. By regulating micro-aeration at different levels, results showed that ORP −420 ± 10 mV promoted maximal hydrolysis efficiency ( η H ), to as high as 49.5% above the control (without micro-aeration). However, organics were markedly lost by over oxidation beyond the optimal ORP. Sub-thermophilic (45 °C) was also proven as effective ( p ≥ 0.05) as thermophilic (55 °C) temperature for hydrolysis with η H 89% higher than that of the ambient (mesophilic) temperature. In continuous digestion studies, the two-stage operations, achieved by adding a pre-hydrolysis (pHY) reactor (HRT 1 day) to the main PF reactor (HRT 4 days), were assessed under four retrofitting schemes. Results showed incremental improvements of each strategy applied and suggested the best overall system configuration of pHY 45 C − 420 mV + PF 45C with sludge re-hydrolysis. Methane yield was improved by 20.4% over the original PF digester operation. Next Generation Sequencing indicated significant changes in abundance and diversity of the major groups of organisms by the sub-thermophilic temperature that linked to the augmented biomethanation performance. Preliminary cost-benefit analysis is also presented. A full-scale implementation in a pilot farm in Thailand is under development. Graphical Abstract: ga1 Highlights: Advanced retrofitting schemes to piggery waste digestion were experimentally tested. Pre-hydrolysis via micro-aeration is effectively controlled by redox potential. Hydrolysis/acidogenic efficiency at 45 °C statistically equals to thermophilic 55 °C. Sludge re-hydrolysis was proven the most effective scheme to enhance CH4 yield. Changes in microbial abundance and diversity at 45 °C are linked to CH4 yield rise.